Evaluation of the Therapy Protocols and Vaccines Applied in the COVID-19 Pandemic - Ozbey, Gokben; Hanafiah, Alfizah; Sukri, Asif; Zigo, František; Arvaiová, Juliana (Ital Publication, 2023)
Despite a plethora of research on vaccine developments and the adverse effects of the vaccine worldwide, there are several research studies on COVID-19 vaccine hesitancy or rejection. The objectives of this study were to investigate the impact of the COVID-19 vaccine on treatment and the factors that contributed to the vaccine concerns. Methods: After one month of being approved by the ethics committee, a descriptive cross-sectional research was conducted using online resources. Samples were randomly selected from the study population. The current study included adults (>18 years old) who were randomly selected from different provinces of Turkey. Results: Most participants were young adults 18–23 years old (47.9%), female (64.8%), married (36.1%), with university education (70.4%), and without medical illness (60.9%) (mean age = 28 years old). Both vaccination doses were given to 53% of the individuals. The most frequent symptom was discomfort at the injection site (0.14%), followed by asthenia muscle pain (0.01%) and edema (24.5%) at the injection site. More symptoms were reported by women than by men. Social media accounts and websites of professional organizations, namely the Dental Association, the Ministry of Health, and the World Health Organization (WHO), were the main sources of COVID-19 information. Hesitancy was induced by concerns about side effects (67.7%), safety (69.7%), lack of information (43.1%), inadequate data on the vaccine clinical trials (55.9%), lack of information on how long protective and effectiveness of vaccines (69.4%), lack of information on how effectiveness against variants (74.8%), think COVID-19 is not dangerous (69.7%), not effectiveness (22.6%) of the vaccine, not safe (32.6%), change my genetic make-up and cause it reproductive sterilite (20.2%), high number of deaths due to COVID-19 (60.8%), the presence of dangerous materials such as aluminum, mercury and others in the content of vaccines, concerns about the country producing the vaccine (38.2%), being afraid of the injection (22%), being against vaccination in general (11%), negative news in the press and social media (38.6%), being risky for only people over 60 (15.9%), having a strong immune system (38.4%), religious (4.7%) and cultural factors (7.4%), believing in natural and traditional medicine (25.4%), and being influenced by friends or family members (19.6%). Hesitancy to accept the COVID-19 vaccine was observed in subjects with hypercholosterolemia and diabetes mellitus. In conclusion, Vaccine hesitancy was primarily related to safety apprehensions. Educational and demographic traits were associated with vaccine admissibility. © 2023 by the authors.
Keywords: COVID-19; Therapy; Vaccine